Attentional function and basal forebrain cholinergic neuron morphology during aging in the Ts65Dn mouse model of Down syndrome - Powers, Brian E. (Brain Struct Funct, 2015)
Individuals with Down syndrome (DS) exhibit intellectual disability and develop Alzheimer's disease-like neuropathology during the third decade of life. The Ts65Dn mouse model of DS exhibits key features of both disorders, including impairments in learning, attention and memory, as well as atrophy of basal forebrain cholinergic neurons (BFCNs). The present study evaluated attentional function in relation to BFCN morphology in young (3 months) and middle-aged (12 months) Ts65Dn mice and disomic (2N) controls. Ts65Dn mice exhibited attentional dysfunction at both ages, with greater impairment in older trisomics. Density of BFCNs was significantly lower for Ts65Dn mice independent of age, which may contribute to attentional dysfunction since BFCN density was positively associated with performance on an attention task. BFCN volume decreased with age in 2N but not Ts65Dn mice. Paradoxically, BFCN volume was greater in older trisomic mice, suggestive of a compensatory response. In sum, attentional dysfunction occurred in both young and middle-aged Ts65Dn mice, which may in part reflect reduced density and/or phenotypic alterations in BFCNs.